Analysis of Sediment Organic Matter Content and Macrozoobenthos Abundance in Padang and Pariaman Coastal Waters, West Sumatra - Azizul Fauzan; Syahril Nedi; Dessy Yoswaty (Jurnal Perikanan dan Kelautan, 2023)
The research was conducted in June - August 2022 in the coastal waters of Padang and Pariaman, West Sumatera. The method used in this research was a survey method. This research aims to determine the organic matter content of the sediment, the abundance of macrozoobenthos, and the relationship between sediment organic matter and the quantity of macrozoobenthos. Sampling was designed by purposive sampling by using 20x30 cm2 Ekman grab. The organic matter content of sediments in the Padang and Pariaman Coastal Waters, West Sumatra, ranged from 4.09 to 7.53%. The average abundance of macrozoobenthos at the four stations ranged from 20.37 to 90.74 ind/m2. Based on the identification results, the macrozoobenthos class found in the coastal waters of Padang and Pariaman consists of Bivalvia, Gastropods, and Malacostraca. The analysis of the sediment organic matter showed weak position relationships with macrozoobenthos abundance.